Pola Asuh Ibu Balita dalam Pemberian Makan pada Anak Stunting - Pekabanda, Kartini; Toru, Veronika; Mila, Antonetha R H; Radandima, Ester (Poltekkes Kemenkes Kupang, 2021)
Introduction: Stunting is a condition of growth failure in children under five years of age (toddlers). The condition of growth failure that occurs in toddlers is caused by a lack of nutritional intake over a certain period of time, as well as repeated infections, especially in the First 1,000 Days of Life (HPK). One of the indirect causes of stunting is the parenting pattern of the toddler's parents. Data on stunting in the Kananggar Health Center Work Area amounted to 204 cases. Objective: The purpose of this study was to determine the description of the parenting pattern of mothers of toddlers in providing food to stunted children in the Kananggar Health Center Work Area, East Sumba Regency. Method: This type of research uses a descriptive method, the population of this study were all mothers of toddlers in the Kananggar Health Center Work Area, the number of samples was 30 people, the sampling technique used Simple Random Sampling by survey from house to house. The research instrument used a questionnaire sheet and was analyzed univariately. Results: Parenting patterns of mothers in feeding toddlers in the Kananggar Health Center Working Area from 30 respondents who used permissive parenting patterns were 25 people (83.3%), Neglect 3 people (10%) and Democratic 2 people (6.6%).